STRATEGI COPING SISWA SMPN 180 JAKARTA UNTUK MENGURANGI STRES AKADEMIK - Afifah Asma Nadia; Anissa Rizky Andriany (As-Sidanah, 2025)
The increasing amount of stress that occurs in the educational environtment is experienced by students because they feel less able to deal with academic demands. This background of the community service activities carried out at SMPN 180 Jakarta, especially for students in class 8C. This community service program is carried out through psychoeducation with the theme “Little Steps of Coping Stress”, which includes expository teaching, discussion, module provision, and practice of butterfly hug techniques which aim to equip students with effective coping strategies to reduce the academic stress they experience. PKM activities are carried out using the Participatory Action Research (PAR) method with a qualitative approach and purposive sampling technique to select participants who experience academic stress. The results of the implementation showed a decrease in academic stress experienced by students, increased understanding of coping strategies, and their readiness to face academic pressure more adaptively as evidenced by the evaluation through the results of the pre-test, post-test, and two-week assistance. This shows that the psychoeducation was successful in helping students reduce their academic stress levels.